P54 Vascular adhesion protein-1: a key player in the modulation of hepatic fibrosis. (16th November 2010) - Weston, C; Haughton, E L; Westerlund, N M; Claridge, L C; Pravin, J; Smith, D J; Adams, D H
Abstract : Introduction: Vascular adhesion protein-1 (VAP-1) is a membrane-associated amine oxidase present on sinusoidal endothelium that supports lymphocyte recruitment to the liver. We have recently detected increased expression of VAP-1 in cirrhotic livers, and reported that a circulating soluble form is elevated in patients with fibrotic liver disease leading us to propose that VAP-1 plays a broader role in hepatic fibrosis. Aim: To investigate the role of VAP-1 in the initiation, progression and resolution of hepatic fibrosis. Method: Human: The distribution and expression of VAP-1 was investigated using multicolour confocal microscopy of normal and diseased human liver. Hepatic stellate cells (aHSC) and activated liver myofibroblasts (aLMF) were isolated from human liver tissue. Cell proliferation was studied using CyQuant. Apoptosis was investigated using a caspase-3 flow cytometry approach and cell detachment assay. Cell spreading was evaluated using xCELLigence impedence measurements. Modified Boyden chambers were used to assess cell migration. Mouse: Liver fibrosis was induced by CCl4 administration in wild-type C57BL/6 mice, wild-type mice dosed with anti-"VAP"-1 antibody and VAP-1 null mice. The degree of fibrosis and inflammatory infiltrate was assessed during active fibrosis and subsequent resolution using immunohistochemistry and qRT-PCR. Results: VAP-1 was present on sinusoids and vascular endothelium in normal human liver but was markedly increased in expanded septa in fibrotic disease where it co-localised with markers of HSC and aLMF (CD90, -SMA) and extracellular matrix (ECM). Increased VAP-1 levels also correlated with the accumulation of advanced glycation end products in the scar, suggestive of a link between amine oxidase activity and modification of ECM. Cultured human aHSC and aLMF expressed VAP-1 mRNA and produced enzymatically active VAP-1 protein. Purified, soluble VAP-1 was a potent promigratory signal for lymphocytes and aHSC in vitro, possibly through amine oxidase activity. Soluble VAP-1 did not induce aHSC apoptosis or proliferation but was associated with an increase in cell spreading. A role for VAP-1 in CCl4-induced liver fibrosis was confirmed in vivo. Both wild-type mice treated with a blocking anti-VAP-1 antibody and VAP-1null mice showed significantly reduced fibrosis after 8 weeks CCL4 compared with wild-type, and had accelerated resolution of fibrosis after cessation of CCl4. Wild-type mice receiving CCl4 also showed a significant increase in VAP-1 and elastin mRNA levels, mature macrophages, CD45-positive infiltrate and serum VAP-1 levels above that observed for VAP-1 null animals or those receiving antibody. Conclusion: These data suggest a multifunctional role for VAP-1 in liver disease in which VAP-1 not only supports lymphocyte and HSC recruitment but also modulates ECM remodelling and fibrogenesis.